Analysis of commercial fishing landings in Yarinacocha (Ucayali, Peru) between 2015-2019 - Salazar-Ramírez, Lilia Enny (2021)
The statistics of landing of fresh and chilled fish in Yarinacocha lake during the period 2015 to 2019 were analysed, considering: total landings and landings by species (in metric tons - t), fishing gear, fishing locations and number of trips. The catch per unit effort (CPUE) was expressed in t * fishing trip-1. The results indicate that landings were relatively higher in 2016 (815 t), although without significant differences between years. The monthly landings showed significant differences mainly between the months of “high waters” (January-April) with months of “low waters” (July-August), which confirms the influence of river levels, where landings increase in low waters (July-September) and decrease in high waters (January-March). In landings by trophic category, detritivores dominated in “high waters” and omnivores in “low waters”. Species of the orders Siluriformes and Characiformes were dominant, especially Pterygoplichthys spp "carachama" and Prochilodus nigricans "boquichico". The most important fishing gears for their contribution to landing were gillnets and purse seines, while hooks also stood out due to the frequency of use.